Folded Resonator for Glucose Solution Density Detection Based on Airy Beam Arrays - Jin, Long; Xiang, Yang (Frontiers in Physics, 2022)
We presented an investigation on the evolution properties of the finite Airy beam array (FAiBA) in metamaterial’s slab system constituting of right-handed materials and double negative materials combining the generalized Huygens–Fresnel integral equation and the light transfer matrix. The beam intensity distribution on the receiver plane and its side transmission view on the (z, x) plane are demonstrated numerically with several array numbers. Moreover, we put forward a kind of folded resonator to detect glucose solution density based on the derived principle and conclusion; the influence of curvature radius on the emerging beam’s evolution characteristics is discussed, and the empirical formula between FAiBA’s received power and glucose solution density is derived by using the fit linear analysis. We hope that the present concept and the derived conclusions can be employed for monitoring in the environmental field, as well as the biomedical and food safety detection.